Autocrine vitamin D signaling switches off pro-inflammatory programs of TH1 cells - Chauss, Daniel; Freiwald, Tilo; McGregor, Reuben; Yan, Bingyu; Wang, Luopin; Nova-Lamperti, Estefania; Kumar, Dhaneshwar; Zhang, Zonghao; Teague, Heather; West, Erin E.; Vannella, Kevin M.; Ramos-Benitez, Marcos J.; et al. (Nature immunology, 2022)
The molecular mechanisms governing orderly shutdown and retraction of CD4 + type 1 helper T (T H 1) cell responses remain poorly understood. Here we show that complement triggers contraction of T H 1 responses by inducing intrinsic expression of the vitamin D (VitD) receptor and the VitD-activating enzyme CYP27B1, permitting T cells to both activate and respond to VitD. VitD then initiated the transition from pro-inflammatory interferon-γ + T H 1 cells to suppressive interleukin-10 + cells. This process was primed by dynamic changes in the epigenetic landscape of CD4 + T cells, generating super-enhancers and recruiting several transcription factors, notably c-JUN, STAT3 and BACH2, which together with VitD receptor shaped the transcriptional response to VitD. Accordingly, VitD did not induce interleukin-10 expression in cells with dysfunctional BACH2 or STAT3. Bronchoalveolar lavage fluid CD4 + T cells of patients with COVID-19 were T H 1-skewed and showed de-repression of genes downregulated by VitD, from either lack of substrate (VitD deficiency) and/or abnormal regulation of this system. During homeostasis T H 1 cells activate a cell-intrinsic inflammatory shutdown program and shift to IL-10 production. Chauss et al. find that this T H 1 homeostatic program is dependent on vitamin D signaling and is disrupted in severe COVID-19.